Efektivitas Nilai EC (Elektrical Conductivity) Terhadap Produksi Selada Merah (Lactuca sativa L.) Varietas Red Rapid Pada Sistem Hidroponik Rakit Apung. - Rommy Andhika Laksono (Paspalum: Jurnal Ilmiah Pertanian, 2020)
This study aims to determine the effect of EC value (Electrical Conductivity) which is able to provide the best production of Red Lettuce (Lactuca sativa L.) Red Rapid Variety on the Floating Raft Hydroponic System. The experiment was conducted in a green house located in Sukaluyu Village, Telukjambe Timur District, Karawang Regency, from October to December 2016. The study used a randomized block design, consisting of 4 treatments, repeated 6 times, namely A (EC 0.5 - 1.5 mS / cm), B (EC 1.5 - 2.5 mS / cm), C (EC 2 , 5 - 3,5 mS / cm), D (EC 3,5 - 4,5 mS / cm) Data were analyzed using analysis of variance and further tests with Duncans multiple range test at 5% level. The number of plants for each treatment plot was 6 plants. The experimental results show that different EC (Electrical Conductivity) values have significantly different effects on the average plant height, 7, 14, 21, 28, 35 and 42 HST, the average number of leaves 21, 28, 35 and 42 HST , average stem diameter 7, 14, 21, 28, 35 and 42 days, average leaf area per plant, and average fresh weight per plant. The EC value of 3.5 - 4.5 mS / cm gives the highest production on the average fresh weight per lettuce plant (158.66 g), equivalent to 31.73 tons / ha.